The pigeon will ride the roller coaster! - Willems, Mo (New York : Union Square Kids, 2022)
Pigeon experiences a loop-de-loop of emotions before his first roller coaster ride.
Ages 3 to 5.
Grades K-1.
AD90L
Decoding demand: 75 (high) Semantic demand: 92 (very high) Syntactic demand: 33 (low) Structure demand: 72 (high)
Keywords: Pigeons -- Juvenile fiction; Emotions -- Juvenile fiction; Roller coasters -- Juvenile fiction; Picture books